Program Analysis and Verification Spring 2015 Program Analysis and Verification Lecture 4: Axiomatic Semantics I Roman Manevich Ben-Gurion University
Agenda Basic concepts of correctness Axiomatic semantics (pages ) – Hoare Logic – Properties of the semantics – Weakest precondition 2
Tentative syllabus Semantics Natural Semantics Structural semantics Axiomatic Verification Static Analysis Automating Hoare Logic Control Flow Graphs Equation Systems Collecting Semantics Abstract Interpretation fundamentals LatticesFixed-Points Chaotic Iteration Galois Connections Domain constructors Widening/ Narrowing Analysis Techniques Numerical Domains Alias analysis Interprocedural Analysis Shape Analysis CEGAR Crafting your own Soot From proofs to abstractions Systematically developing transformers 3
program correctness 4
Program correctness concepts Property = a certain relationship between initial state and final state Partial correctness = properties that hold if program terminates Termination = program always terminates – i.e., for every input state 5 partial correctness + termination = total correctness Other correctness concepts exist: liveness, resource usage, … Main focus of this course
Factorial example Factorial partial correctness property = if the statement terminates then the final value of y will be the factorial of the initial value of x – What if x < 0? Formally, using natural semantics: …? 6 S fac y := 1; while (x=1) do (y := y*x; x := x–1) S fac, ’ implies ’ y = ( x )!
Verifying factorial with natural semantics 7
Natural semantics for While 8 x := a, [x A a ] [ass ns ] skip, [skip ns ] S 1, ’, S 2, ’ ’’ S 1 ; S 2, ’’ [comp ns ] S 1, ’ if b then S 1 else S 2, ’ if B b = tt [if tt ns ] S 2, ’ if b then S 1 else S 2, ’ if B b = ff [if ff ns ] while b do S, if B b = ff [while ff ns ] S, ’, while b do S, ’ ’’ while b do S, ’’ if B b = tt [while tt ns ]
Staged proof 9
Stages 10 y := 1; while (x=1) do (y := y*x; x := x–1) ss’s’ s’ y = (s x)! s x > 0 while (x=1) do (y := y*x; x := x–1) y := y*x; x := x–1 ss’’ s y (s x)! = s’’ y (s’’ x)! s x > 0 ss’’ s y (s x)! = s’’ y (s’’ x)! s’’x = 1 s x > 0
Inductive proof over iterations 11 while (x=1) do (y := y*x; x := x–1) (y := y*x; x := x–1) while (x=1) do (y := y*x; x := x–1) ss’’ s y (s x)! = s’’ y (s’’ x)! s’’x = 1 s x > 0 s s’s’ s’s’ s’’ s’ y (s’ x)! = s’’ y (s’’ x)! s’’x = 1 s’ x > 0 s y (s x)! = s’ y (s’ x)! s x > 0
First stage 12
Second stage 13
while (x=1) do (y := y*x; x := x–1), s s’ 14
Third stage 15
How easy was that? Proof is very laborious – Need to connect all transitions and argue about relationships between their states – Reason: too closely connected to semantics of programming language Proof is long – Makes it hard to find possible mistakes How did we know to find this proof? – Is there a methodology? 16
17 Can you prove my program correct? I’ll use operational semantics Better use axiomatic verification
18 "P. Oxy. I 29" by Euclid - Licensed under Public Domain via Wikimedia Commons - One of the oldest surviving fragments of Euclid's Elements, a textbook used for millennia to teach proof-writing techniques. The diagram accompanies Book II, Proposition 5
A systematic approach to program verification 19
Axiomatic verification approach What do we need in order to prove that the program does what it supposed to do? 20 Specify the required behavior: express properties Compare the behavior with the one obtained by the operational semantics Develop a proof system for showing that the program satisfies a requirement Mechanically use the proof system to show correctness
Axiomatic semantics contributors C.A.R. Hoare Robert Floyd Edsger W. Dijkstra : use assertions as foundation for static correctness proofs 1969: use Floyd’s ideas to define axiomatic semantics “An axiomatic basis for computer programming”An axiomatic basis for computer programming Predicate transformer semantics: weakest precondition and strongest postcondition
Assertions, a.k.a Hoare triples P and Q are state predicates expressed as logical formulas – Example: x >0 If P holds in the initial state, and if execution of C terminates on that state, then Q will hold in the state in which C halts C is not required to always terminate {true} while true do skip {false} 22 { P } C { Q } precondition postcondition statement a.k.a command
Total correctness assertions If P holds in the initial state, execution of C must terminate on that state, and Q will hold in the state in which C halts 23 [ P ] C [ Q ]
Specifying correctness of factorial 24
Factorial example: specify precondition/postcondition 25 { ? } y := 1; while (x=1) do (y := y*x; x := x–1) { ? }
First attempt 26 { x >0 } y := 1; while (x=1) do (y := y*x; x := x–1) { y = x ! } Holds only for value of x at state after execution finishes We need a way to “remember” value of x before execution
Fixed assertion 27 { x =n } y := 1; while (x=1) do (y := y*x; x := x–1) { y =n! n>0 } A logical variable, must not appear in statement - immutable
The proof outline 28 { x=n } y := 1; { x>0 y*x!=n! n x } while (x=1) do { x-1>0 (y*x)*(x-1)!=n! n (x-1) } y := y*x; { x-1>0 y*(x-1)!=n! n (x-1) } x := x–1 { y*x!=n! n>0 x=1 } { n!*(n+1) = (n+1)! } Background axiom
Formalizing partial correctness via hoare logic 29
States and predicates – program states (State) – undefined A state predicate P is a (possibly infinite) set of states P – P holds in state 30 P
FO Logic reminder We write A B if for all states if A then B – { | A } { | B } – For every predicate A: false A true We write A B if A B and B A – false 5=7 In writing Hoare-style proofs, we will often replace a predicate A with A’ such that A A’ and A’ is “simpler” 31
Formalizing Hoare triples { P } C { Q } – , ’ . ( P C, ’) ’ Q alternatively – Convention: P for all P . P S ns C Q 32 P C(P)C(P) Q ’’ C Why did we choose natural semantics? S ns C = ’ if C, ’ else
Formalizing Hoare triples { P } C { Q } – , ’ . ( P C, * ’) ’ Q alternatively – Convention: P for all P . P S sos C Q 33 P C(P)C(P) Q ’’ C S sos C = ’ if C, * ’ else
How do we express predicates? Extensional approach – Abstract mathematical functions P : State {tt, ff} Intensional approach – via language of formulae 34
An assertion language Bexp is not expressive enough to express predicates needed for many proofs – Extend Bexp Allow quantification – z. … – z. … z. z = k n Import well known mathematical concepts – n! n (n-1) 2 1 35
An assertion language 36 a ::= n | x | a 1 + a 2 | a 1 a 2 | a 1 – a 2 A ::= true | false | a 1 = a 2 | a 1 a 2 | A | A 1 A 2 | A 1 A 2 | A 1 A 2 | z. A | z. A Either a program variables or a logical variable
37 Some FO logic definitions before we get to the rules
Free/bound variables A variable is said to be bound in a formula when it occurs in the scope of a quantifier Otherwise it is said to be free – i. k=i m – (i+100 77) i. j+1=i+3) FV(A) the free variables of A Defined inductively on the abstract syntax tree of A 38
Computing free variables 39 FV ( n ) {} FV ( x ) { x } FV ( a 1 + a 2 ) FV ( a 1 a 2 ) FV ( a 1 - a 2 ) FV ( a 1 ) FV ( a 2 ) FV ( true ) FV ( false ) {} FV ( a 1 = a 2 ) FV ( a 1 a 2 ) FV ( a 1 ) FV ( a 2 ) FV ( A ) FV ( A ) FV ( A 1 A 2 ) FV ( A 1 A 2 ) FV ( A 1 A 2 ) FV ( a 1 ) FV ( a 2 ) FV ( z. A ) FV ( z. A ) FV ( A ) \ { z }
Substitution An expression t is pure (a term) if it does not contain quantifiers A[t/z] denotes the assertion A’ which is the same as A, except that all instances of the free variable z are replaced by t A i. k=i m A[5/k] = …? A[5/i] = …? 40
Calculating substitutions 41 n[t/z] = n x[t/z] = x x[t/x] = t (a 1 + a 2 )[t/z]= a 1 [t/z] + a 2 [t/z] (a 1 a 2 )[t/z]= a 1 [t/z] a 2 [t/z] (a 1 - a 2 )[t/z]= a 1 [t/z] - a 2 [t/z]
Calculating substitutions 42 true[t/x] = true false[t/x] = false (a 1 = a 2 )[t/z]= a 1 [t/z] = a 2 [t/z] (a 1 a 2 )[t/z]= a 1 [t/z] a 2 [t/z] ( A)[t/z]= (A[t/z]) (A 1 A 2 )[t/z]= A 1 [t/z] A 2 [t/z] (A 1 A 2 )[t/z] = A 1 [t/z] A 2 [t/z] (A 1 A 2 )[t/z] = A 1 [t/z] A 2 [t/z] ( z. A)[t/z] = z. A ( z. A)[t/y] = z. A[t/y] ( z. A)[t/z] = z. A ( z. A)[t/y] = z. A[t/y]
43 and now… the rules six are completely enough
Axiomatic semantics for While 44 { P[a/ x ] } x := a { P } [ass p ] { P } skip { P } [skip p ] { P } S 1 { Q },{ Q } S 2 { R } { P } S 1 ; S 2 { R } [comp p ] { b P } S 1 { Q }, { b P } S 2 { Q } { P } if b then S 1 else S 2 { Q } [if p ] { b P } S { P } { P } while b do S { b P } [while p ] { P’ } S { Q’ } { P } S { Q } [cons p ] if P P’ and Q’ Q Notice similarity to natural semantics rules What’s different about this rule?
Assignment rule A “backwards” rule x := a always finishes Why is this true? – Recall operational semantics: Exercises: {?} x:=y*z {x 8} {?} x:=y*z {w=5} 45 x := a, [ x A a ] [ass ns ] [xAa] P[xAa] P
skip rule 46 skip, [skip ns ]
Composition rule Holds when S 1 terminates in every state where P holds and then Q holds and S 2 terminates in every state where Q holds and then R holds 47 S 1, ’, S 2, ’ ’’ S 1 ; S 2, ’’ [comp ns ]
Condition rule 48 S 1, ’ if b then S 1 else S 2, ’ if B b = tt [if tt ns ] S 2, ’ if b then S 1 else S 2, ’ if B b = ff [if ff ns ]
Loop rule Here P is called an invariant for the loop – Holds before and after each loop iteration – Finding loop invariants – most challenging part of proofs When loop finishes, b is false 49 while b do S, if B b = ff [while ff ns ] S, ’, while b do S, ’ ’’ while b do S, ’’ if B b = tt [while tt ns ]
Rule of consequence Allows strengthening the precondition and weakening the postcondition The only rule that is not related to a statement 50
Rule of consequence 51 Why do we need it? Allows the following {y*z<9} x:=y*z {x<9} {y*z<9 w=5} x:=y*z {x<9}
Next lecture: axiomatic semantics II